Atomic‐Level Strain Sensing and Piezoresistance Effect in a 1D Single‐Atom Chain - Zhi Qu; Wenqi Zhang; Shuideng Wang; Donglei Chen; Yiqing Yao; Mingxing Cheng; Lixin Dong (Advanced Science)
Abstract Small variations in interatomic distances have a substantial impact on the physical and chemical properties of nanomaterials. Investigating these effects offers a deeper understanding of the mechanisms governing the behavior of nanomaterials and nanostructures, providing foundations for the design and optimization of novel functional materials. However, the impact of strain in single‐atom structures on piezoresistance and electronic transport properties remains unclear. This study focuses on a 1D, dynamic functional nanostructure that uses interatomic distance variations for lattice‐level strain sensing. This silver (Ag) atom chain shows a high stability at room‐temperature and an exceptional piezoresistance coefficient, enabling the detection of structural changes at atomic radius scale with high sampling frequencies. It is considered that this strong piezoresistivity is due to the impact of interatomic distance on electron scattering and transport mechanisms. The density functional theory simulations of electron transport reveal that variations in interatomic distance significantly influence the relaxation time of electron scattering and the effective electron mass, thereby modulating the characteristics of electron transport. This 1D dynamic nanostructure has the potential to address the low time resolution limitations of transmission electron microscopy (TEM), enhancing its capabilities for in situ characterization and multi‐physical‐field sensing. This study provides experimental evidence for insights into atomic scale piezoresistivity and underlying mechanisms.